2014
DOI: 10.1016/j.jcjd.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypoglycemia on Health-Related Quality of Life: Canadian Results from a Multinational Time Trade-off Survey

Abstract: The findings presented here show that any form of hypoglycemia had a negative impact on HRQoL in a Canadian population. Nocturnal and/or severe hypoglycemia had a greater negative impact on HRQoL compared with daytime and/or non-severe events. This highlights the importance of preventing the development and nocturnal manifestation of hypoglycemia in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 40 publications
3
53
2
Order By: Relevance
“…Our study found that an increase in severity of hypoglycaemia was associated with a significant and clinically relevant decrement in both physical and mental health component of HRQoL and overall health utility. Previous studies conducted in the UK, United States, Canada and Brazil have also shown self‐reported hypoglycaemic symptoms to be independently associated with reduced HRQoL, and that the magnitude of this reduction increases with both the severity and frequency of the symptoms . A recent study also demonstrated a significant relationship between experiencing low blood sugar symptoms and decreased HRQoL, decreased utility and greater difficulties with mobility, daily activities, pain/discomfort and anxiety/depression, relative to patients who did not report those symptoms …”
Section: Discussionmentioning
confidence: 85%
“…Our study found that an increase in severity of hypoglycaemia was associated with a significant and clinically relevant decrement in both physical and mental health component of HRQoL and overall health utility. Previous studies conducted in the UK, United States, Canada and Brazil have also shown self‐reported hypoglycaemic symptoms to be independently associated with reduced HRQoL, and that the magnitude of this reduction increases with both the severity and frequency of the symptoms . A recent study also demonstrated a significant relationship between experiencing low blood sugar symptoms and decreased HRQoL, decreased utility and greater difficulties with mobility, daily activities, pain/discomfort and anxiety/depression, relative to patients who did not report those symptoms …”
Section: Discussionmentioning
confidence: 85%
“…The disutility value of a NSHE was difficult to ascertain due to diverse definitions of NSHEs within a limited literature. Prior studies of the QoL effects of NSHE (38,39) were based on life with and without symptomatic hypoglycemia or on the experience of a single symptomatic hypoglycemic event. These patient-reported definitions are distinct from the new international definition of ,54 mg/dL for $20 successive minutes (21), attainable by CGM device, which has a higher frequency than those based on past definitions and is frequently asymptomatic.…”
Section: Psamentioning
confidence: 99%
“…Hypoglycemia is common when insulin treatment is intensified and is a consideration when insulin strategies and glycemic targets are selected (1). Hypoglycemia is a major concern for patients living with diabetes (2), who may take actions to reduce the incidence of hypoglycemia (3), which has been associated with fear, anxiety and depression (4,5), reduced healthrelated quality of life, reduced productivity and increased healthcare costs (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%